Perancangan Pengendalian Proses Berbasis Seni Perang Sun Zi Untuk Meningkatkan Kinerja Karyawan Pada Divisi Produksi: Studi Pada PT Belantara Subur - Eko Rahmad Fitriyadi; Sujoko Efferin (Akuntansi dan Teknologi Informasi, 2018)
This research is applied research that aims to provide recommendations related to the needs of organizational understanding of process control. After seeing still not effective and efficient organization in applying process control. The role of process control methods is important to help companies maintain the compliance of members of the organization against applicable standards. The purpose of this research is to see how the role of process control based on Sun Zi's Art of War as an alternative for the organization in applying effective and efficient process control. The author uses qualitative methods by way of observation, interview and document analysis in order to support the validity of data. The main object of this research is PT. Belantara Fertile. The scope of this research is on the organization's production division which is considered to require better control. Based on the findings obtained during the study, the authors can conclude that the process control based on Sun Zi War Art is one of the interesting methods to apply. Therefore, the process control based on Sun Zi's Art of War can be considered and can be applied by other organizations.